Securing black lion tamarin populations: improving habitat-based inputs and risks for population viability analysis to inform management decisions - Forero-Sánchez, Francy; Rezende, Gabriela Cabral; Valladares-Pádua, Cláudio; Vannucchi, Fabio Stucchi; Jerusalinsky, Leandro; Pacca, Luciana; Traylor-Holzer, Kathy (Frontiers in Conservation Science, 2025)
Wild populations across the globe face an escalating risk of decline and potential extinction due to a variety of threats. Key among these are habitat loss and degradation, which results in smaller, isolated populations that are vulnerable to stochastic effects. The Endangered black lion tamarin (Leontopithecus chrysopygus) survives in 17 fragments of the Atlantic Forest within the Paranapanema River basin, in southeast Brazil, with an estimated 2,255 individuals. Life history and threat data from the 2005 Population Viability Analysis (PVA) for this species were updated and augmented, including new estimates of environmental resistance factors present in, or projected for, their habitat. Notably, improved estimates of carrying capacity for this species were developed using a plant-based energetic model. Climate change and fire risk data were incorporated to project future carrying capacity, and habitat connectivity supported estimates of black lion tamarin dispersal across this fragmented landscape. The resulting population viability projections using Vortex simulation software identify core subpopulations with low extinction risk and high gene diversity, as well as smaller subpopulations with low long-term viability, highlighting the need for targeted conservation strategies across the fragmented metapopulation.